Working through a pandemic: The mediating effect of nurses' health on the relationship between working conditions and turnover intent - Farinaz Havaei; Xuyan Tang; Nassim Adhami; Megan Kaulius; Sheila A. Boamah; Kimberly McMillan (Nursing Open, 2023)
Abstract Aim While research has demonstrated that nurses' health and working conditions are important predictors of turnover in COVID‐19, the relationship between these factors is not well understood. Our study investigated the mechanism through which working conditions and nurses' physical and mental health could impact intent to leave the nursing profession. Design Secondary data from a cross‐sectional survey of 3478 nurses in British Columbia administered in May 2021 were analysed using structural equation modelling. Methods Two models were assessed utilizing workplace conditions as the predictor, nurses' health as the mediator, and reported turnover intent (Model 1), and anticipated time to turnover (Model 2) as the outcomes. Results Nurses' health partially mediated the relationship between working conditions and turnover intent, where poorer workplace conditions were directly and indirectly associated with greater likelihood of leaving the profession. Nurses' health fully mediated the relationship between working conditions and nurses' anticipated time to turnover, after controlling for age. The findings from this study underscore the importance of enhancing working conditions and improving nurses' mental health and safety on the job. Patient or Public Contribution The British Columbia Nurses' Union provided the data for this study; survey data from 3478 nurses were utilized in our study.